Developmental environment of the mastership program; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Kornienko N. A. Nina Alekseevna (2016, 2016)
Title screen